2008
DOI: 10.1128/jvi.01047-08
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Matrix Protein 1-Specific Human CD8+T-Cell Response Induced in Trivalent Inactivated Vaccine Recipients

Abstract: Among 17 HLA-A2-positive healthy adults, CD8؉ T-cell responses against an HLA-A2-restricted matrix protein 1 (M1) epitope increased after immunization with trivalent inactivated influenza vaccine (TIV) in two individuals. The presence of M1 in TIV was confirmed by Western blotting. T-cell cytotoxicity assays showed that TIV is processed and the epitope is presented by antigen-presenting cells to an M1 epitope-specific CD8 ؉ T-cell line for specific lysis. These data show that TIV, which is formulated to contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
4
24
0
2
Order By: Relevance
“…Here we showed that TIV (GlaxoSmithKline) induced HLA-A2/M1 58-66 -tetramer ϩ CD8 ϩ T cells in 20% of HLA-2-positive individuals, as this vaccine contains a relatively high level of M protein (11). Consistent with our finding, recent studies also showed that TIV (Sanofi Pasteur) could induce HLA-A2/M1-tetramer ϩ CD8 ϩ T cells in 12 to 25% of HLA-2-positive individuals (45,51). Live attenuated influenza vaccine (LAIV) is expected to induce T-cell responses more efficiently than TIV, as it contains all the viral internal proteins.…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivsupporting
confidence: 80%
See 1 more Smart Citation
“…Here we showed that TIV (GlaxoSmithKline) induced HLA-A2/M1 58-66 -tetramer ϩ CD8 ϩ T cells in 20% of HLA-2-positive individuals, as this vaccine contains a relatively high level of M protein (11). Consistent with our finding, recent studies also showed that TIV (Sanofi Pasteur) could induce HLA-A2/M1-tetramer ϩ CD8 ϩ T cells in 12 to 25% of HLA-2-positive individuals (45,51). Live attenuated influenza vaccine (LAIV) is expected to induce T-cell responses more efficiently than TIV, as it contains all the viral internal proteins.…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivsupporting
confidence: 80%
“…Since there is a very low frequency of influenza virus-specific T cells in human peripheral blood, most studies have used IFN-␥ responses to investigate the cross-reactive T-cell responses or have used influenza virus peptide-pulsed cell lines or cell lines in which HA, NA, and M proteins are expressed as target cells to determine the cross-reactive CTLs of in vitroexpanded CD8 T-cell lines (5,23,29,51). However, these assays have some limitations.…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 99%
“…Although only 31% of the B-cell epitopes were conserved, 41% of the CD4 ϩ and 69% of the CD8 ϩ T-cell epitopes were conserved. It is known that crossreactive T-cell immune responses can exist even between serologically distinct influenza A strains (14,15). Based on this observation and the data presented above, we hypothesized that it is possible that immune memory responses against S-OIV exist in the adult population, at the level of both B and T cells.…”
Section: Discussionmentioning
confidence: 83%
“…This might be explained by that the ELISA measures IgG against epitopes from the hemagglutinin, the neuraminidase and trace amounts of the matrix 1 protein. [28][29][30][31] Apart from the neutralization epitopes of HA, these other epitopes may be beneficial in Ab-dependent cell-mediated cytotoxicity and complement fixation.…”
Section: Discussionmentioning
confidence: 99%